Analisis Karakteristik Transmisi LoRa pada Wilayah Perkotaan - Muhammad Muhajir Kurniawan; Kasyful Amron; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
LoRa is one of the access technologies in Wireless Sensor Networks that has the advantage of a high range of distances. LoRa data transmission is influenced by Spreading Factor, Bandwidth, Transmission Power and Coding Rate. There are studies that observe the characteristics of LoRa by using wite gaussian noise generators as an interference. However, the study was conducted at a distance of 10 meters, so further research needs to be carried out on the capabilities of the LoRa network in real environments. This study focuses on observing the transmission characteristics of LoRa in urban areas. The system consists of 1 sensor node device and 1 gateway device. The implementation and testing process was carried out in the campus area of Universitas Brawijaya, Malang City. The gateway is placed at a height of 45 meters above ground level in a multi-storey building. Node sensors are placed at multiple locations in the campus environment. The test was carried out by observing the Success Ratio, Roundtrip Delay and RSSI. From the results of the analysis carried out, a larger Spreading Factor value and a smaller Bandwidth are suitable for transmission of distances of more than 250 meters with a high Success Ratio value. While the smaller Spreading Factor value and larger Bandwidth are suitable for use in transmission distances of less than 250 meters. A larger Tranmission Power results in better RSSI sensitivity than smaller Transmission Power. The farthest transmission distance that can be reached is 700 meters with a Success Ratio percentage of 73% with a Spreading Factor of 11. Based on the tests that have been carried out, LoRa can be implemented in urban environments with several conditions such as the use of higher Spreading Factor, lower Bandwidth and medium Transmission Power.